Pengaruh Pendekatan Kontekstual Dan Motivasi Belajar Terhadap Prestasi Belajar Fisika Siswa Kelas XI SMU Negeri Nino Konis Santana Dan SMU Negeri Lere Anan Timor Di Kecamatan Lospalos - Estáquio Amaral; Maria Lia Felizarda Freitas; Egidius Dewa (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
The low quality of education in schools, especially in science subjects, is attributed to the insufficient competence of science teachers in addressing learning challenges. Teachers are perceived as unresponsive and employ monotonous teaching methods, making the learning process dull. The issue of educational quality is also influenced by the lack of consistent motivation and discipline among students. As leaders in the classroom, teachers play a key role in influencing students' interests and learning outcomes. Creative teachers using varied methods can enhance students' learning interests. This writing highlights the importance of a contextual approach in physics education, making the material more relevant and engaging for students, boosting motivation, and strengthening problem-solving skills. The research utilizes a quantitative method with questionnaires and documentation to assess the impact of the contextual learning approach on motivation and physics learning achievement. The results show a positive and significant effect of the contextual learning approach on motivation and physics learning achievement. Consequently, teachers need to implement a teaching approach relevant to student's daily lives and encourage intrinsic motivation to improve their physics learning achievement. This research provides crucial insights for the development of teaching methods and an understanding of the factors influencing the quality of education in Timor-Leste.